Do green spaces protect night sleep duration and sleep quality in children and adolescents? Evidence from 10 observational studies - Huilei Wu; Xiaolong Su; Qingqing Yu; Ruowen Wang; Yating Li; Han Hu; Qian Zhang; Zhenhui Yang; Yuhan Li; Weidong Wu; Guofu Zhang; Hui Wu (BMC Public Health)
Abstract Background More than half of children and adolescents do not get the recommended eight hours of sleep necessary for optimal growth and development. Since sleep was very important for the growth and development of children and adolescents, it is necessary to improve the environment for children and adolescents to sleep. Green space have been found to improve sleep in general, and the aim of this systematic review is to assess the association of green space on sleep among children and adolescents. Methods The PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database and Wan Fang database were searched from the establishment of these databases to July 31, 2024. Newcastle - Ottawa Scale (NOS) and Joanna Briggs Institute (JBI) scale were applied to evaluate the quality of the included studies. Stata17.0 was used to draw forest maps and sensitivity analysis was performed on the results of meta-analysis to evaluate the stability of the results. Publication bias was assessed using funnel plots and Egger test method. Results A total of 10 articles with 102,873 participants meeting the criteria were included in this study, including 6 articles were cohort studies and 4 articles were cross-sectional studies. The sample sizes ranged from 328 to 63,352 participants per study. The results show that green space have a positive association on night sleep duration in children and adolescents (OR: 0.969, 95%CI [0.869, 1.079] and OR: 0.949, 95%CI [0.854, 1.055]). Conclusions The results show that green space have a positive association on night sleep duration in children and adolescents. The association of green space on sleep quality and napping could be further studied in the future.